Renal biochemistry profile in guinea pigs (Cavia porcellus) fed with pisonay (Erythrina sp) - Rodrigo-Condori, Noemi T. (2020)
The experiment was carried out in the district of Tamburco, province of Abancay, Peru, between January and April 2017 and aimed to determine serum levels of creatinine, urea and blood urea nitrogen (BUN) in guinea pigs fed with pisonay (Erythrina sp). Leaves and petioles of pisonay with four months of regrowth and fresh alfalfa (Medicago sativa) with 28 days of regrowth were used in the diet of 18 improved male guinea pigs. The animals were distributed in three treatments: A100: 100% alfalfa (80 g), A50P50: 50% alfalfa (40 g) plus 50% pisonay (40 g) and P100: 100% pisonay (80 g). The feed was provided twice a day. Serum creatinine levels in guinea pigs fed A50P50 and P100 were significantly higher compared to those that consumed A100 (p<0.05). The BUN levels were only significantly different between A100 and P100 (p<0.05), while there were no significant differences between treatments for the case of blood urea. The proportional increase of 50 to 100% of pisonay leaves as fresh forage in the diet of guinea pigs could cause disorders in kidney function.